A new survey to the nonlinear electrical transmission line model - Ozer, Ozen; Baskonus, Haci Mehmet; Bulut, Hasan; Amirali, Ilhame; Yel, Gulnur (KeAi Communications Co., 2021)
In this paper, we find new travelling wave solutions to the nonlinear electrical transmission line model. Exponential function method is applied. This model is used to the voltage behaviors in electrical transmission lines. Under a suitable choice of control parameters, we plot the figures along with contour surfaces of new solutions by using computational programs such as Mathematica, Maple and Matlab. Some information about the behavior of voltage on the electrical lines is extracted. The hyperbolic, periodic or singular properties are reported. © 2021
Keywords: Complex and hyperbolic function solutions; Exponential function method; Nonlinear electrical transmission line model in (2 + 1)-dimension equation